Prognostic Value of N1/N2 Neutrophils Heterogeneity and Tertiary Lymphoid Structure in Hepatocellular Carcinoma Patients - Yanfei Lang; Weiwei Fu; Wei Xu; Chao Ma; Xiuyun Tian; Chunyi Hao; Shigang Ding (Cancer Medicine)
ABSTRACT Background The tumor immune microenvironment, including neutrophils and tertiary lymphoid structures (TLSs), is pivotal for HCC prognosis assessment. Tumor‐associated neutrophils exhibit plasticity, adopting either an antitumorigenic N1 (MPO+ CD206−) or a pro‐tumorigenic N2 (MPO+ CD206+) phenotype. We explored the prognostic value of neutrophil plasticity and TLS maturity in HCC in both tumor and peritumoral tissues and addressed their interaction. Methods A retrospective cohort of 79 HCC patients who underwent radical resection from 2015 to 2018 was analyzed, with complete clinical characteristics and survival data of more than 5 years. Multiplex immunohistochemistry identified N1/N2 neutrophils and TLS maturity. Survival differences and correlations with clinical features were assessed. Results HCC patients were divided into high‐ and low‐level groups on the basis of the N1 and N2 classifications of neutrophils, revealing a positive correlation with prognosis in tumor tissues and a negative one in peritumoral tissues. TLS maturity stages were associated with prognosis, with a higher proportion of secondary TLS (SFL‐TLS) in peritumoral tissues correlating positively with survival. Further analysis of the correlation between neutrophils and TLSs revealed that most neutrophils infiltrated outside of the TLS in the peritumoral tissues of patients with HCC, and the proportions of SFL‐TLSs and N1 cells in the peritumoral tissue were negatively correlated and positively correlated with survival. Both univariate and multivariate analyses revealed that the N1/N2 ratio in peritumoral tissues was an independent prognostic predictor of HCC. Conclusions The N1/N2 ratio of neutrophils and the proportion of SFL‐TLS are considered important prognostic indicators that may reflect the immune microenvironment of HCC patients.